Coherently Manipulated 2D Ion Crystal in a Monolithic Paul Trap. Issue 11 (14th October 2020) - Wang, Ye; Qiao, Mu; Cai, Zhengyang; Zhang, Kuan; Jin, Naijun; Wang, Pengfei; Chen, Wentao; Luan, Chunyang; Du, Botao; Wang, Haiyan; Song, Yipu; Yum, Dahyun; et al.
Abstract: Using a 2D ion crystal for quantum simulation and computation has been pursued for a long time. The coherent manipulation of a stationary 2D crystal in the Paul trap may be hampered by the micromotion synchronous with the oscillating electric field. Here, a simple Paul trap that stably confines over 20 171 Yb + ions in a stationary 2D crystal is presented. The disturbance of the micromotion in coherent operations is mitigated by making the direction of micromotion perpendicular to the transverse direction of the 2D crystal. To achieve the condition of perpendicularity, the structure of the trap electrodes is comprehensively designed, which also provides the controllability of rotating principal axes. The transverse vibrational modes by Raman laser‐beams are addressed and coherent evolution of sideband transitions on these modes observed. Moreover, this trap allows for optical access with a 0.86 numerical aperture which facilitates applying individually addressing laser‐beams. This work can be an example of realizing a 2D‐trapped‐ion based quantum simulator and computer in a Paul trap. Abstract : It is demonstrated how 2D ion crystals in a Paul trap can be used for quantum information processing. We mitigate the disturbance of the micromotion in the coherent operations, which is the main bottleneck of the 2D crystal, and perform quantum operations on the transverse vibrational modes of the 2D ion‐crystals. This work opens a way of realizing a 2D‐trapped‐ion based quantum simulator in Paul traps.